فحوص ماقبل الصياغة لتحضير علكة طبية لمادة سيترات السيلدينافيل - ابراهيم, وهاد (Latakia University Journal -Medical Sciences Series, 2018)
Medicated chewing gum is a solid dosage form intended for local or systemic effect. This study aimed to prepare medicated chewing gum of Sildenafil citrate to improve the patient compliance, stress accompanied with sexual dieses as well as to alleviate the side effects. Five different formulations were prepared. They differ in the softner’s kind (lecithin, Glycerin) and its concentration. As a part of the preformulation study we investigated the compatibility between the Sildenfil citrate and the other excipient as well as the flowability of the mixtures. In addition the prepared tablets were characterized (dimension, weight, hardness and friability) and the effect of the softner on the dissolution rate of the drug was examined. The result showed the good compatability between the Sildenafil citrat and the used excipients. The used plasizer showed no impact on the flowiblity or on the dissolution rate. تعتبر العلكة الطبية من الأشكال الصيدلية الفموية المستخدمة للمعالجة الموضعية أو الجهازية. إن الهدف من هذه الدراسة هو تحضير علكة طبية لمادة السيلدنافيل سيترات بهدف تحسين مطاوعة المريض وتخفيف التوتر المترافق مع الأمراض الجنسية بالإضافة إلى تخفيف الآثار الجانبية الناتجة عن المادة الفعالة. تم تحضير خمس صيغ مختلفة عن بعضها بشكل رئيسي بوجود مادة مطرية (ليستين, غليسرين) وبتركيز هذه المادة. ضمن دراسات ماقبل الصياغة تم التحري عن توافق المادة الدوائية مع السواغات ثم تأثير تركيز المادة المطرية على الانسيابية أما بعد تحضير المضغوطات فقد تمت دراسة الخصائص العامة للمضغوطات (أبعاد, تجانس وزن, قساوة وهشاشية) بالإضافة إلى تأثر سرعة تحرر المادة الفعالة بنوع المادة المطرية وتركيزها. لم تظهر الدراسة أي تنافر بين السيلدنافيل والسواغات المستخدمة. لم تُظهر المواد المطرية أي تأثير على انسيابية المزيج أو على خصائص المضغوطات الناتجة.